A multifunctional metasurface with broadband absorption and high-efficiency transmission polarization conversion. (1st November 2022) - Fu, Yang; Yang, Helin; Cheng, Houyuan; Liu, Shanshan; Li, Shangru; Zhang, Aidong; Wen, Dinge
Abstract: In this paper, a polarization-sensitive absorption and transmission polarization conversion multifunctional metasurface is designed. Based on the principle of Fabry-Borot antenna, the modulation of electromagnetic waves with different polarizations is realized. Receiver-transmitter structure consisting of rectangular metal patches on the front and back sides . Cross-polarization conversion of Y-polarized waves was achieved at 8.9–15.2 GHz. In combination with the open-slit elliptical structure, selective absorption of X-polarization can be achieved, thus realizing the radar cross-section(RCS) reduction of the target. The absorption operates in the frequency band of 8.3–13.9 GHz. Electromagnetic waves of different polarizations do not affect each other in the modulation of the same structure and operate in almost the same frequency band. To verify the proposed structure, the relevant parameters were optimized and measured. The experimental results match with the simulation results, and the design can be used for radome and electromagnetic stealth.